2018
DOI: 10.1186/s13024-018-0240-1
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated phosphorylation of Rab GTPases by LRRK2 induces neurodegeneration

Abstract: BackgroundMutations in leucine-rich repeat kinase 2 (LRRK2) are the most common cause of familial and sporadic Parkinson’s disease (PD). Elevated kinase activity is associated with LRRK2 toxicity, but the substrates that mediate neurodegeneration remain poorly defined. Given the increasing evidence suggesting a role of LRRK2 in membrane and vesicle trafficking, here we systemically screened Rab GTPases, core regulators of vesicular dynamics, as potential substrates of LRRK2 and investigated the functional cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 58 publications
3
93
0
Order By: Relevance
“…The existence of Rab10 in the tyrosine hydroxylase positive neurons controlling vision and proboscis movement argues that LRRK2 might indeed phosphorylate Rab10 directly. Thus our in vivo results both support the in vitro (biochemical and cell culture) data in which LRRK2 directly phosphorylates Rab10 (3)(4)(5)(6)(7)(8), but also suggest a separate pathway for LRRK2-G2019S action. Further, while Rab3 is also phosphorylated by LRRK2 in vitro (3), it did not synergise with LRRK2-G2019S in the visual assay, and was not detected in the MC neurons .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The existence of Rab10 in the tyrosine hydroxylase positive neurons controlling vision and proboscis movement argues that LRRK2 might indeed phosphorylate Rab10 directly. Thus our in vivo results both support the in vitro (biochemical and cell culture) data in which LRRK2 directly phosphorylates Rab10 (3)(4)(5)(6)(7)(8), but also suggest a separate pathway for LRRK2-G2019S action. Further, while Rab3 is also phosphorylated by LRRK2 in vitro (3), it did not synergise with LRRK2-G2019S in the visual assay, and was not detected in the MC neurons .…”
Section: Discussionsupporting
confidence: 86%
“…A number of studies highlighted a diverse range of >30 proteins that might be phosphorylated by LRRK2, suggesting it is a generalised kinase (2). However, several research teams have recently reported that LRRK2 is a more specific kinase, phosphorylating Rab GTPases (3)(4)(5)(6)(7)(8). However, it is not clear which of the more than 60 Rabs are actually phosphorylated in vivo.…”
Section: Significance Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Rab7L1 was found to be phosphorylated by LRRK2 and is involved in vesicular clearance through the trans-Golgi network (Liu et al, 2017). It was shown that LRRK2, phospho-Rab 8/10 together with Rab7L1 help to maintain homeostasis in stressed lysosomes Jeong et al, 2018) and phosphomutants of Rab proteins at conserved LRRK2 phosphorylation sites induces neurotoxicity and dopaminergic neuron degeneration in mice (Jeong et al, 2018). In human iPS neurons, in wild-type and LRRK2 mutated neurons, it was shown that LRRK2 may be playing a role by phosphorylating auxilin in its clathrin domain at Ser627 which is abolished upon kinase inhibition (Nguyen and Krainc, 2018), and transmission electron microscopy showed decreased synaptic vesicle density in presynaptic nerve terminals of R1441C dopaminergic neurons indicating defective synaptic vesicle endocytosis (Nguyen and Krainc, 2018).…”
Section: Lrrk2 (Leucine-rich-repeat Kinase 2)mentioning
confidence: 99%
“…They influence biology by interacting with a series of effector proteins when complexed to GTP. LRRK2 phosphorylates Rab proteins at a highly conserved Ser/Thr residue located at the center of the effector binding region of these enzymes that is also known as the Switch-II motif [7, 26,28]. This phosphorylation event appears to act in two ways.…”
Section: Introductionmentioning
confidence: 99%